Der DAX-Future: Kursverhalten und Arbitragemöglichkeiten - Wolfgang Bühler; Alexander Kempf (Kredit und Kapital, 1993)
The DAX Futures Contract: Price Trends and Arbitrage Possibilities The following contribution analyzes the behaviour of DAX futures contracts in their first year of existence using all transaction prices. It thus presents the first comprehensive study of stock index futures contracts whose underlying is a performance index. It turns out that, in spite of this special characteristic of the underlying, the DAX futures contracts have behaved in much the same way as future rates agreements. The greater volatility of the DAX futures contract compared with the DAX may be attributed to the existence of "stale prices" in the index. This contribution demonstrates for the price ratio between the cash and the futures markets that DAX futures contracts have been significantly undervalued compared with the price that can be referred to as fair according to cash-and-carry arbitrage. Such undervaluation increases with the residual lifetime, but is not dependent on the liquidity of the market. An ex-ante analysis shows that, even when transactions costs depend on the residual lifetime and delays in implementating deals are taken into consideration, it was possible in the period under review to make arbitrage gains almost without risk. However, the number of opportunities for making such gains decreases in level over time.
Keywords: 330